MEP: Malaysia enteral product apps for dietitian in Hospital Serdang - Ali, Siti Khadijah; Kamarulzaman, Fatin Faniza; Ismail, Nuha (Semarak Ilmu Publishing, 2024)
Enteral nutrition is an essential nutrition therapy that provides a complete source of nutrition for malnourished patients. Hence, dietitians will advise them to follow a complete diet. However, up to now, dietitians at Hospital Serdang have been facing difficulties due to the unsystematic storage of information on enteral products, and they are required to memorize all the nutrients of the products. To overcome this issue, a MEP (Malaysia Enteral Product) application for Dietitians was proposed to assist dietitians at Hospital Serdang. The MEP application was developed using the Agile methodology model. Agile was chosen because it is flexible and can be modified if required. Functions such as searching, viewing, comparing, and analysing products were included. As an initial observation, six dietitians from Hospital Serdang tested the MEP. All respondents were required to share their feedback using a provided Google form. Based on the feedback, all respondents agreed that the MEP application was able to provide precise enteral nutritional information and was able to reduce time and energy during the evaluation and planning of enteral nutrition interventions for patients. © 2024, Semarak Ilmu Publishing. All rights reserved.